THE BLENDED LEARNING ACCOMPLISHMENT OF COMPUTER AND NETWORK ENGINEERING EXPERTISE PROGRAM IN VOCATIONAL SCHOOLS - Aries Alfian Prasetyo; Setiadi Cahyono Putro; I Made Wirawan (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
This study aims to (1) describe supporting and inhibiting factors in blended learning implementation for the students of computer and network engineering expertise program and (2) describe the accomplishment level of the implementation. This study is designed as a descriptive study with quantitative approach. The research object is the blended learning implementation in computer and network engineering expertise program in SMK N 1 Baureno Bojonegoro. The research subjects consist of teachers, facilities, materials and applications and students in the blended learning implementation process. The data was collected using observation, surveys and interviews. It was analyzed using percentages and classification analysis. The results reveals that the blended learning has been appropriately implemented. It is proven by the analysis result of supporting and inhibiting factors including facilities, teachers’ skill, materials and applications and blended learning accomplishment. The result is also supported by the description about blended learning activity, the use of facilities, blended learning composition and the impact of implementing blended learning. The weaknesses in the implementation process are the low quantity and quality of personal computers and inadequate internet connection. Teachers and school boards are expected to work collaboratively to solve the problems thus the implementation of blended learning can be maximized.